MEASURES TO IMPROVE THE QUALITY OF FLUFF - Azambayev, Mukhammadjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
According to the lint quality improvement plan, the following practical studies were carried out; based on the optimization of the parametrization of the final cleaning of seeds from weed impurities in the new selection mesh device, a new linter design was developed, by establishing a selection, mesh device that works intensively and provides seed cleaning without violating the technological regulations of the linter machine, rational parameters of the new linter were determined and recommended by implementation, as a result, positive economic efficiency was obtained, according to the results of theoretical and practical research and compared with the data of the existing linter and the new projection, mesh linter, with the adaptation, positive conclusions were obtained on the objectivity of the results of the study. The significance of the study’s results is determined by the cleaning of seeds over all the surfaces of the mesh vibrating surfaces, as well as by the regularity of the release of weed impurities from the devices.